Weed interference with Lupinus albus crop - Gaspar, Natália (1996)
A comparative analysis of the growth of Lupinus albus grown in stands in mixture with annual weeds and in stands without weeds (with herbicide) was carried out on a field trial with two large plots. The measurements taken at every two weeks include some parameters wich characterize the growth of above ground L. albus individual plants (height, number of leaves, number of plants/unit area, total dried weight and their components and leaf area). At the same intervals the above ground dried weight of weed species was determined. Logistic curves werw fitted to primary values and to growth parameters. The annual weeds werw highly dominated by Medicago nigra, Melilotus segetalis, Papaver rhoeas, Phalaris brachystachis + P. coerulescens, Raphanus raphanistrum and Sinapis arvensis. Leaf area, relative growth rate (RGR), leaf area ratio, number of L. albus plants/unit area, harvest index (HI), crop growth rate (CGR), leaf area index (LAI) in stands without weeds (with herbicide) were significantly higher than in stands in mixture with weeds.